1999
DOI: 10.1051/agro:19990706
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of indirect selection in determining the quality of bread wheat for French bread-baking

Abstract: Putting together information on French bread-baking drawn from 15 years of multi-local experimentation and results of various technological tests (protein content and grain hardness, Pelshenke test, Zeleny sedimentation test and Chopin alveograph), has made it possible to study the effects of genotype and environment on the traits tested as well as the relationships between them. With the exception of protein content and extensibility L of alveograph, genotype x environment interactions are weak for technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…That confirmed previous results which stated the difficulty of indirect selection for French bread-making (Oury et al 1999). Several explanations can be stated:…”
Section: Validation Of the Pls Equationssupporting
confidence: 92%
See 1 more Smart Citation
“…That confirmed previous results which stated the difficulty of indirect selection for French bread-making (Oury et al 1999). Several explanations can be stated:…”
Section: Validation Of the Pls Equationssupporting
confidence: 92%
“…Thus, for a long time, breeders have used indirect phenotypical small-scale tests like SDS, Pelshenke, Zeleny or mixograph tests (for an outlook, see Branlard et al 1991), to assess wheat grain quality during the early generations of the breeding process, where the lines evaluated are numerous and the quantities of grains low. The quality of the prediction enabled by these tests is quite good for end-use characters like dough strength or some types of tin loaf Dobraszczyk et al 2005), but remains low for French bread-baking (Oury et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…SDS sedimentation volume for bread making quality) are used in earlier generations. However, several studies showed a week relationship between indirect test parameters and the final test scores [57]. If a line with desirable quality parameters could be identified in early generations, this would allow us to 1) discard undesirable lines in early generations, and 2) evaluate a larger number of populations or greater number of lines within each population at the earlier generations (head-row stage).…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, protein content was weakly correlated with tenacity (P) (r = 0,26 ), dough strength (W) (r = 0,34) and extensibility (L) (r = 0,27). Previous results showed weak correlation between protein content and P, W and L (Branlard y Dardevet, 1985;Rasper et al, 1986;Oury et al, 1999, Bordes et al, 2008. For example, in a study of 15 years in multi-site trials, the determination coefficients of protein content were 0.24, 0.11 and 0.08 for W, P and L, respectively (Oury et al, 1999).…”
Section: Protein Contentmentioning
confidence: 90%
“…Later, Pomeranz et al, (1990) have also found very weak correlations between protein content and kernel hardness. Oury et al, (1999), in a 15year survey of new varieties, found no correlation between protein content and hardness.…”
Section: Protein Contentmentioning
confidence: 94%